2020
DOI: 10.1186/s12903-020-01128-0
|View full text |Cite
|
Sign up to set email alerts
|

Dental expenditure, progressivity and horizontal inequality in Chinese adults: based on the 4th National Oral Health Epidemiology Survey

Abstract: Background: The financial burden of oral diseases is a growing concern as the medical expenses rise worldwide. The aim of this study was to investigate the dental expenditure, analyze its progressivity and horizontal inequality under the general health finance and insurance system, and identify the key social determinants of the inequality for Chinese adults. Methods: A secondary analysis used the data of 13,464 adults from the 4th National Oral Health Epidemiological Survey (NOHES) in China was undertaken. Th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 30 publications
(30 reference statements)
1
10
0
Order By: Relevance
“…As in a previous study in China, 8 Chinese medical reform, especially reform of the dental system, has much room for improvement. 40 The results of the decomposition analyses supplement previous findings that socioeconomic-related inequality in dental care service utilization cannot be comprehensively explained by those variables influencing the affordability of dental care payments, which further suggests that this inequality may not be eliminated only by providing financial support. 10 Mirroring previous research that also found that education 5,8,14 and residential location 8 contributed to inequality in the use of oral health services, the present study suggests that educational attainment and residential location have more of an impact among younger adults aged 35-44 years than among older adults.…”
Section: Discussionsupporting
confidence: 71%
“…As in a previous study in China, 8 Chinese medical reform, especially reform of the dental system, has much room for improvement. 40 The results of the decomposition analyses supplement previous findings that socioeconomic-related inequality in dental care service utilization cannot be comprehensively explained by those variables influencing the affordability of dental care payments, which further suggests that this inequality may not be eliminated only by providing financial support. 10 Mirroring previous research that also found that education 5,8,14 and residential location 8 contributed to inequality in the use of oral health services, the present study suggests that educational attainment and residential location have more of an impact among younger adults aged 35-44 years than among older adults.…”
Section: Discussionsupporting
confidence: 71%
“…First, income inequality may lead to the reduction of investment on the public health resources such as water fluoridation [ 42 , 43 ]. Secondly, the percentage of routine expenditure on health care is low among the low-income group and the dental expenditure is still a tiny fraction in terms of the health care payments in China [ 44 ]. Besides, studies showed that people with low incomes tend to neglect health-related behaviors such as smoking and regular health care [ 21 , 22 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…14 According to previous studies, dental service utilization among Chinese preschool children may be influenced by caregiver education background, socioeconomic status, perception of their children's oral health status, dental insurance dental fear and demographic factors. 16 Although some studies have found socioeconomic-related inequalities in dental service utilization among adults in China, [17][18][19] the evidence related to inequality in children's dental service utilization is insufficient.…”
Section: Introductionmentioning
confidence: 99%
“…19,[22][23][24] Inequality in dental care utilization among Chinese adults has been measured in previous studies by means of CI. [17][18][19] However, evidence related to inequality in dental care indicating that dental care utilization in children aged 3-5 years was concentrated in those who were better off. The contribution of the need variables to socioeconomicrelated inequality in dental services was minimal, and most dental care utilization inequality could be explained by household income, caregiver education attainment and urban-rural disparities, accounting for 32.0%, 49.4% and 20.4% respectively.…”
Section: Introductionmentioning
confidence: 99%